REGULASI HUKUM KEJAHATAN TRANSNASIONAL TERKAIT NARKOTIKA DI INDONESIA DAN THAILAND - Taufiq, Muhammad; Haryadi, Wicaksono Putra; Saputra, Angga (The Juris, 2025)
The use of advanced technology, sophisticated operandi modes, cross-border operations, and extensive network of organizations in support of international drug crime have caused many victims, especially among the younger generation, and have had a serious impact on the lives of individuals, communities, and nations. This research uses a methodological approach to normative law, involving legal theory and comparative law research. This article aims to evaluate the effectiveness of the agreements implemented in Thailand and Indonesia in stopping illicit drug trafficking. Nevertheless, the policies that have been implemented to end the illicit drug trade from both countries have not shown success in attempts to stop or mitigate the problem.